Optimization and Kinetics of Solid Liquid Extraction of Malaysian Jatropha Curcas Seeds - Sayyar, Sepidar (2009)
The Jatropha is a plant which grows in most of tropical and subtropical regions of the world. The oil from the Jatropha seeds can be used as fuel alternative and for making biodiesel. This work aimed to determine the optimum parameters to achieve maximum oil yield in solid liquid extraction of Jatropha seeds under experimental conditions. The optimum condition was then applied in ultrasound assisted and microwave pretreatment extraction methods to determine the amount of yield. The kinetics of the extraction was also studied based on the assumption of a second order mechanism. The extraction was carried out using a soxhlet extractor equipped with condenser and hot plate. The effects of five main factors which are namely type of solvents, temperature, solvent to solid ratio, reaction time and size of the raw material were investigated experimentally on the solid liquid extraction of Jatropha seed to optimize the extraction process. The optimum condition was found at eight hours reaction time, temperature of around 68°C, coarse particle size (0.5-0.75 mm), solvent to solid ratio of 6:1 (v/w) and using hexane as the solvent. The maximum amount of yield at optimized condition was at 47.3 % by wt. The activation energy was found to be 7145.05 (J/mol) and the highest initial extraction rate was calculated to be and 4.21 (g/L min). The maximum amount of oil extracted by ultrasound assisted and microwave pretreatment methods were 51.4 and 49.4% respectively. The oil extracted by conventional, ultrasound assisted and microwave pretreatment extraction methods contained, respectively, 0.62, 0.67 and 0.63% free fatty acid and 98.3, 97 and 97.7% triglyceride.